Economists in the Americas: Convergence, divergence and connection (2009)
This collection of essays, the first comparative study of economics and economists in the Americas, is published just as the crafting of a new hemispheric identity is widely debated. The United States and Latin America, with their centuries-old history of conflict and collaboration, offer a rich setting for comparative analyses. Both are important reference points in the field of economics. Since the Second World War, the US has provided the most richly endowed home for the expansion of modern economics.